Adaptabilidade de bovinos taurinos criados em condições climáticas subtropicais - Baena, Marielle Moura (2014)
Although Brazil is one of the largest meat producers worldwide, producers have herds with low productivity. Thus, many cattle raisers seek genetically superior animals from temperate climates; however, the change to a tropical climate may lead to a decline in productive performance. The aims of this study were to examine adaptability characteristics (morphological, physiological, molecular) of the Angus and Simmental cattle breeds to subtropical climate conditions. We studied 145 bull of the two genetic groups with an average age of 15 months that were part of performance testing (PT) in confinement on the Fazenda Santa Éster (Santa Ester Farm) in Silvianopolis, MG. For the first study of morphological and physiological evaluations, 73 animals of the two breeds were used. Measurements of hair length (HL, cm), number of hairs (NH, hair/cm2), and hair coat thickness (HC, mm) were obtained in July (winter) and November (spring) of 2012. Physiological measurements, such as respiratory rate (RR, breaths/min) and coat temperature (CT, °C), as well as the temperature and humidity index (THI) were obtained from August to November in the morning and afternoon. The least square method was used for analyses of variance. In the second study, 72 Angus bulls were used. After DNA extraction, 20 samples of extreme animals (10 positive extreme and 10 negative extreme) for the characteristics of RR and CT were amplified in the regions of interest and sequenced, and SNP type markers were sought and characterized. Angus animals had the highest HC and HL. In the winter season, the HL, NH, and HC were greater, regardless of the breed. In the interaction, it was observed that in the spring, the HC and HL characteristics did not differ according to breed. The animals were under thermal comfort, according to THI. The effect of breed, time, and day was observed for RR and CT. Angus had the highest mean for RR and, in general, the mean values of RR and CT were higher in the afternoon. In the HSF1 gene, no SNP changes amino acids in the protein, but in the HSPA6 gene, four SNPs change. The presence of TagSNP was detected in the HSF1 gene, with maximum disequilibrium region of r2 = 0.87 and MAFs from 0.10 to 0.50, and MAFs from 0.02 to 0.21 in the HSPA6 gene. Hardy Weinberg equilibrium shifts were observed in the SNPs of genes, and half the loci had heterozygosity greater than 50%. Behavior of the breeds is similar in the hotter season of spring, and the data suggest that there is great genetic variation in genes, which may contribute to identification and selection of cattle more thermotolerant to the subtropical climate.